2020
DOI: 10.3390/cancers12030696
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health-Related Quality of Life in Women with Breast Cancer in the Middle East: A Systematic Review

Abstract: Objectives: The aim of the present systematic review was to identify the factors that potentially influence health-related quality of life (HRQoL) in women with breast cancer (BC) in the Middle East. Methods: A systematic search of the PubMed, Ovid Medline, Cochrane, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, and Ebscohost databases was conducted to identify all relevant articles published in peer-reviewed journals up to April 2018. The keywords were "Health related qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
4
25
0
5
Order By: Relevance
“…The results of this study indicated that medical comorbidities, anxiety/depression, and BI highly in uence QoL among women who have undergone major BC surgeries. These results appear to have been veri ed by other studies in Asia and other countries in terms of the key determinants in uencing the QoL of women with major breast cancer surgeries from a long-term perspective [6,16,29,39,[47][48][49]72]. Additionally, women undergoing BC surgeries who received hormone therapy less than one year post-surgery positively related their long term QoL items to sexual activity due to balancing hormones and expressed gratitude for the ability to mitigate menopausal and vaginal symptoms, increase their BI and self-esteem, maintain their sexual desire, and continue interactive, friendly relationships (in the case of young BC survivors), all of which contribute to their long-term sexual health [20,42].…”
Section: Discussionsupporting
confidence: 65%
“…The results of this study indicated that medical comorbidities, anxiety/depression, and BI highly in uence QoL among women who have undergone major BC surgeries. These results appear to have been veri ed by other studies in Asia and other countries in terms of the key determinants in uencing the QoL of women with major breast cancer surgeries from a long-term perspective [6,16,29,39,[47][48][49]72]. Additionally, women undergoing BC surgeries who received hormone therapy less than one year post-surgery positively related their long term QoL items to sexual activity due to balancing hormones and expressed gratitude for the ability to mitigate menopausal and vaginal symptoms, increase their BI and self-esteem, maintain their sexual desire, and continue interactive, friendly relationships (in the case of young BC survivors), all of which contribute to their long-term sexual health [20,42].…”
Section: Discussionsupporting
confidence: 65%
“…While two other studies [8,22] found that younger patients' QOL were more affected than older patients and the reason behind to this suggest that inability to ful ll themselves as wives and they need better physical appearance than older patients. The nding of these studies was supported by other systematic review conducted in Middle East of breast cancer patients which states that there was inconsistency between studies regarding the effect of age on HRQOL [34]. The review also identi ed that patients with higher level of education has better QOL than illiterate; this is due to those who are educated may have better access to salaried and employment and get better economic resource that brings good sense of control.…”
Section: Discussionmentioning
confidence: 72%
“…Despite several recent studies in which the impact of various risk factors on PRES were investigated, the consensus and position statement on these factors on the prognosis of PRES in childhood cancer have still been based on expert opinion and not empirical evidence ( 2 , 8 , 16 , 18 26 ). Therefore, we believe that our studies are warranted by a more focused review of the literature.…”
Section: Introductionmentioning
confidence: 99%